Nutraceuticals for Arthritis Management: Beyond Nutrition, Targeting Inflammation, and Immunity - ., Kritika; Maurya, Neelesh Kumar (Journal of Biomedical and Pharmaceutical Research, 2024)
Nutraceuticals, bridging the gap between "food" and "pharmaceuticals," are gaining significant traction in modern healthcare due to their potential to address chronic diseases like arthritis. This shift towards preventative and holistic approaches emphasizes the power of nutrition in managing health. Nutraceuticals encompass a diverse range of bioactive compounds derived from natural sources – vitamins, minerals, plant extracts, proteins, and dietary supplements. Their appeal lies in their purported ability to offer health benefits beyond basic nutrition, including antioxidant, anti-inflammatory, and immunomodulatory properties. Rheumatoid arthritis (RA) presents a significant health concern in India, affecting an estimated 0.75% of adults – exceeding the global average of 0.46%. This prevalence might be linked to genetic similarities between North Indians and Caucasians. Notably, RA affects women more disproportionately. This review explores the potential of nutraceuticals in managing arthritis in India, focusing on their ability to combat inflammation and modulate the immune system, offering benefits beyond simple dietary intervention. Keywords: nutraceuticals, arthritis management, nutrition, targeting inflammation, immunity.